Impact of exercise on quality of life and body-self perception of patients with acromegaly - ÇAMLIGÜNEY, ASİYE FİLİZ; ERKUT, AYŞE OYA; ÇOTUK, HASAN BİROL (SPRINGER, 2014)
In acromegaly the impact of therapy on well-being and self-perception of patients is not clearly defined. The data existing on the effect of treatment on health-related quality of life in patients with acromegaly is inconclusive. In this study we addressed the effect of exercise on health-related quality of life, symptoms of depression and perception of body image in patients with acromegaly. Patients with acromegaly were stratified into two groups according to their participation in a prescheduled program of exercise. Participants in the study group performed exercise for 75 min a day for 3 days a week during cosecutive 3 months. Warming, cardio, strength, balance and stretching moves applied in every course. Both the exercise group and control group were asked to complete a questionnaire on quality of life, symptoms of depression and self-perception of body image. Each questionnaire was answered by both groups before the beginning of the exercise program (at month-0) and after the completion of the program (at month-3). In exercise group after the completion of exercise period there was a tendency towards decreament in body mass index and IGF-I, although not statistically significant (p = 0.08 and p = 0.09). Self-assessment of body image improved significantly after participation in the exercise program (p = 0.01). Present findings support that exercise may be an adjunctive method for patients with acromegaly to improve self esteem and perception.
Keywords: Acromegaly; Exercise; Quality of life; Body-self perception; ACROQOL; QUESTIONNAIRE